PENGAWASAN BADAN PENGAWAS PEMILU (BAWASLU) TERHADAP PELANGGARAN TAHAPAN PEMILIHAN KEPALA DAERAH (PILKADA) DI KOTA DUMAI TAHUN 2020 - Anita Karolin; M.Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Dumai City Election Supervisory Body is an election supervisory institution based on a law that has authority in supervisingregional head elections. One of them is also related to supervision of violations .of the Regional Head Election stage in the City of DumaiThere are reports and findings of violations committed by participants inthe Regionalorganizers Regional Head Election, as well as Regional Head Election (community), it is necessary to supervise for the implementation Regional Head Elections . The results of this study are the Oversight of the Election Supervisory Boardfor violations of the Regional Head Election in Dumai City by Election Supervisory Board , namely 19 violations received Election Supervisory Body stages the Regional Head Election , including at the nomination stage as many as 5 Regional Head Election, then at the campaign stage as many as 11 Regional Head Election, at the voting stage as many as 3 originating from public reports and the findings of the Election Supervisory Board , which are forwarded to agencies for follow-up according to the type of violation which is conducted. The influencing factors supervision of the Regional Head Election, namely: first, sufficient budget factor in the supervision of the Regional Head Election which is Rp. 8,722,032,000 from the Dumai City Government Grant Fund to Election Oversight Body. Second, the Employee Placement Factor, as many as 21 sub-district supervisory committees that are ad hoc in collaboration with the Election Supervisory Board City of Dumai are optimal in carrying out supervision. Third, Coordination Within Institutions Election Supervisory Body which consists of Leadership and Personnel Elements in the Secretariat who coordinate with each other to carry out supervision. Fourth, Technology, Information and Network Factors which are still an obstacle in carrying out supervision seen from one of the Sungai Sembilan Districts that the network is difficult to access. Keywords: Supervision, Regional Head Elections and Offenses.